PENGARUH PERTUMBUHAN PEMUKIMAN TERHADAP AKTIVITAS PEREKONOMIAN DI KELURAHAN KOYA BARAT - Huwae, Pricilia; Ana Rusim, Dewi; Rante, Harmonis (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2024)
This research aims to identify the factors influencing the growth of settlements and economic activities inKoya Barat Village, Muara Tami District, and the efforts made in the growth of settlements and economic activitiesin Koya Barat Village, Muara Tami District. The quantitative research method and data collection techniquesinvolve questionnaires and documentation. The data analysis uses simple linear regression. The results of theresearch indicate that the factors influencing the growth of settlements and economic activities in Koya BaratVillage, Muara Tami District, show that the level of settlement growth in Koya Barat Village, Muara Tami District,is categorized as high, with 65 respondents or 65%. This includes several factors such as the type of physicalbuilding, building/occupant type, wall type, roof type, ceiling, floor type, door, sanitation, window, ventilation,and ridge. The economic level of the community with a very high economic level is 33 respondents or 33%, anda high economic level is 31 respondents or 31%, which means that the economic level of the community in KoyaBarat Village, Muara Tami District is high, including education level, occupation/livelihood, and householdincome. The efforts made in the growth of settlements and economic activities in Koya Barat Village, Muara TamiDistrict, indicate a significant influence of settlement growth on the economy in Koya Barat Village, Muara TamiDistrict, which means that if settlement growth increases, economic activities will also experience a significantincrease.